POSSIBILITIES OF MULTIPARAMETRIC MAGNETIC RESONANCE IMAGING IN THE PERSONALIZATION OF SALVAGE RADIATION THERAPY IN PATIENTS WITH PROSTATE CANCER RECURRENCE - F. A. Kossov; P. V. Bulychkin; B. P. Olimov; V. O. Panov; S. I. Tkachev; Yu. V. Buydenok; N. L. Shimanovskiy; M. A. Shorikov; I. E. Tyurin; B. I. Dolgushin (Вестник рентгенологии и радиологии, 2018)
Objective. To identify the possibility of multiparametrical magnetic resonance imaging (mpMRI) in the diagnosis of clinical recurrence of prostate cancer, with the aim of optimizing salvage radiation therapy (SLT).Material and methods. In this prospective study, the results of 89 patients with marker relapse (PSA) of prostate cancer (PCa) after radical prostatectomy was examined. mpMRI of the pelvis was performed before the SLT and 6 months later. Separately, in 44 patients, the data of dynamic contrast enhancement (DCE) with different contrast agents (gadobutrol, gadodiamide and gadoversetamide) were analyzed.Results. According to the model of multiple linear regression, the area of the substrate of clinical recurrence is statistically significantly correlated with the PSA level (R=0.74, p<0.0008), regardless of the all type of DCE administered. The sensitivity of mpMRI in detection of clinical recurrence of PCa was 92%, specificity 81%, accuracy 88%, which was assessed by comparison with PSA level. The use of the hypofractive radiation dose to the area of clinical recurrence of PCa, detected with mpMRI, showed a more progressive drop of the marker (PSA), compared to the standard SLT scheme (McNemarre test, p<0.03). A statistically significant correlations (by the Mann–Whitney criterion with p<0.018) from the signal change in DCE after the injection of contrast agents (different types) and the substrate area.Conclusion. mpMRI has high sensitivity, specificity and accuracy to detecting the substrate of the clinical recurrence of PCa. The use of DCE for concentration of 1.0 mmol (gadobutrol) significantly increases the reliability of detecting clinical recurrence of PCa, especially when the substrate is found to small and ultrasmall sizes. The application of DCE with the contrast agents at the concentration of 1.0 mmol (gadobutrol) prior to initiation of SLT course, helps to plan the proposed radiation exposure zone, with the aim of providing the necessary for a complete resorption of the recurrent tumor, a high tumor dose of radiation to the clinical recurrence region.